CHRISTOPHER MARLOWE’S “CARP DIEM POETRY” - Majitova Feruza Gayrat qizi; Xamitov Eldorbek Erkin o`g`li (Ta’lim innovatsiyasi va integratsiyasi, 2024)
In this article, we will discuss the life and creative work of Christopher Marlowe. In addition, the article discusses and analyzes Marlowe’s famous works, poems and their genres.